2008
DOI: 10.1007/s10709-008-9255-9
|View full text |Cite
|
Sign up to set email alerts
|

Population cytogenetics of Chironomus circumdatus Kieffer, 1921 (Diptera, Chironomidae) from Thailand

Abstract: The objectives of this study were to explore cytogenetic variation and the role of chromosomal change on local adaptation and genetic differentiation of Chironomus circumdatus Kieffer from Thailand. A total of 1,505 larvae from 24 populations were examined cytologically. Twelve chromosomal inversions were found and most of these (9 of 12) were rare inversions. All populations were in Hardy-Weinberg equilibrium. Significant association (P < 0.001) between the A2 and B5 inversions was detected in one population.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…The value of F ST was similar to those of S. exiguum in Ecuador (F ST ϭ0.083) (Charalambous et al 2005) but much lower than those of S. nakhonense (F ST ϭ0.651) (Pramual 2006), Prosimulium fuscum (F ST ϭ0.421) and Simulium decorum (F ST ϭ0.622) . A significant relationship between the level of genetic differentiation (D A values) and geographic distance (Km) between populations (rϭ0.497, pϭ0.004) suggests that gene flow was limited by geographic distance.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…The value of F ST was similar to those of S. exiguum in Ecuador (F ST ϭ0.083) (Charalambous et al 2005) but much lower than those of S. nakhonense (F ST ϭ0.651) (Pramual 2006), Prosimulium fuscum (F ST ϭ0.421) and Simulium decorum (F ST ϭ0.622) . A significant relationship between the level of genetic differentiation (D A values) and geographic distance (Km) between populations (rϭ0.497, pϭ0.004) suggests that gene flow was limited by geographic distance.…”
Section: Discussionsupporting
confidence: 62%
“…Stalker (1980) found that the standard sequence of the chromosomes of Drosophila melanogaster was involved in adaptation to cold temperature. Pramual et al (2008) found an association between inversions and water temperature in Chironomus circumdatus. Etges et al (2006) found that frequency shifts in the chromosome inversions in D. robusta was a response to recent climatic change.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…While population cytogenetic studies exist for a number of other animals (sparrows: Thomas et al ., , and references therein; grasshoppers: Shaw et al ., ; midges: Pramual et al ., ; water beetles: Aradottir & Angus, ; butterflies: Lukhtanov et al ., ), they remain scarce for mammals where data on karyotypic polymorphisms are surprisingly rare (Coghlan et al ., ), thus limiting our understanding of chromosome‐associated evolutionary processes. In fact, well‐sampled model mammalian taxa that are conventionally recognized as being highly polymorphic usually exist as complexes of (sub)species/races where various cytotypes correspond to geographically fixed karyotypes (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Pramual et al (2008) noted the synonymy of Chironomus plumatisetigerus with Chironomus circumdatus, based on the information of the web page of Martin (2007). That web page is not a recognised publication and, further, the synonymy is not indicated in either the title or abstract of the paper.…”
Section: Sgtb Khalsa College University Of Delhi Delhi Indiamentioning
confidence: 99%